Numerical and Experimental Analysis of Cooling System Performance in Induction Hobs: A Comparison of Heatsink Designs - Ayberk Salim Mayil; Cisil Timuralp (Applied Sciences)
The increasing demand for induction hobs necessitates efficient cooling systems to ensure the safe operation of electronic cut-outs. This study investigates the thermal representation of three different ignition designs integrated into an induction hob cooling system. A simplified model consisting of a radial fan, a daughterboard, and the electronics installed in the systems is used for the maintenance of the system. Remote measurements of air velocities at the cooler outlets are compared with the results obtained through programmable system dynamics (CFD) operations using FloEFD v2021.1 software. The findings of the study using the k-ε turbulence model show that Type 1 temperature is resistant to the lowest surface temperature for both the closest (IGBT 1) and the farthest (IGBT 2) temperature to the fan. Conversely, Type 3 temperatures exhibited high temperatures. Air velocity comparisons showed a maximum error rate of 30%, which is acceptable considering the variability in Type 1. Measurement system evaluation and DOE study were continued to increase the experimental range. This study demonstrates the utility offered by heatsink design in optimizing the cooling system of induction hobs and provides valuable insights for integrating thermal management systems.